Evaluation of a Workplace-Based Sleep Education Program. Issue 9 (September 2016) - Burton, Wayne N.; Chen, Chin-Yu; Li, Xingquan; McCluskey, Maureen; Erickson, Denise; Barone, Daniel; Lattarulo, Charles; Schultz, Alyssa B.
Abstract : Introduction: Poor sleep is common among working adults. Chronic sleep deprivation is associated with health problems. A healthy sleep educational program (using webinars and other intranet-based resources) was offered to employees of a financial services corporation. Methods: In 2015, a total of 357 employees (50% completion rate) completed both a pre- and post-program questionnaire assessing sleep quality and workplace productivity. Results: Many aspects of sleep statistically improved from T1 to T2 for program participants. These included improvements in hours of sleep, sleep quality, ease of getting asleep, feeling rested, nights of poor sleep, job performance, days of sleepiness, and others. Employees reporting any limitation in productivity also showed significant improvement. Conclusions: This workplace healthy sleep intervention was associated with significant improvements in sleep quality and quantity among program participants.